2003
DOI: 10.1200/jco.2003.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Grading of Urothelial Cell Carcinoma With Fibroblast Growth Factor Receptor 3 and MIB-1 is Superior to Pathologic Grade for the Prediction of Clinical Outcome

Abstract: The FGFR3 mutation represents the favorable molecular pathway of UCC. Molecular grading provides a new, simple, and highly reproducible tool for clinical decision making in UCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
213
2
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(235 citation statements)
references
References 38 publications
11
213
2
9
Order By: Relevance
“…As FGFR3 is a gene involved in bladder carcinogenesis and the presence of FGFR3 mutations is also a common event in benign skin tumors, [30][31][32]35,37,41 this association between bladder, skin, and prostate cancer could suggest a common role for FGFR3 in their pathogenesis. However, the mutational analysis of the corresponding bladder tumors and normal prostate samples in some of the patients from our study revealed the wild-type status of the gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As FGFR3 is a gene involved in bladder carcinogenesis and the presence of FGFR3 mutations is also a common event in benign skin tumors, [30][31][32]35,37,41 this association between bladder, skin, and prostate cancer could suggest a common role for FGFR3 in their pathogenesis. However, the mutational analysis of the corresponding bladder tumors and normal prostate samples in some of the patients from our study revealed the wild-type status of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…37 To test the possibility of finding exon 15 mutations in prostate cancer we screened a subgroup of 53 tumors, classified as grade The F386L germline single nucleotide polymorphism (SNP) was detected in two samples (2%), both of them from radical prostatectomy tumors with a combined Gleason score ¼ 7 ( Table 2). The prevalence of this polymorphism in heterozygosity is about 1% (http://www.ncbi.nlm.nih.gov/SNP).…”
Section: Fgfr3 Mutation Analysismentioning
confidence: 99%
“…Although a small percentage of invasive carcinomas are low grade, usually limited to the lamina propria, >95% of Admittedly, controversy remains, and the reasons are multifactorial but mainly due to the fact that the clinical risk of recurrence and progression are determined not solely by growth pattern and grade but also by other factors such as size, multifocality, time to recurrence, and prior intravesical therapy. In addition, we must accept the fact that grading is largely subjective and that, in the future, ancillary studies (either immunohistochemical or molecular assays) will lead to enhanced reproducibility and better correlation with clinical outcome [52].…”
Section: Grading Of Urothelial Tumoursmentioning
confidence: 99%
“…[7][8][9][10][11][12] Also, molecular grading of UCC showed improved predictive potential compared to classical pathological parameters. 13 Despite these advances, no molecular marker is integrated in clinical prognostics yet.In the ongoing search for recurrence-predictive markers, several studies have attempted to molecularly classify bladder tumors by cDNA microarray analysis. 14-18 One of these studies identified a panel of 26 genes, which distinguished between early-recurring and nonrecurring superficial Ta tumors in a cohort of 31 patients.…”
mentioning
confidence: 99%